2020
DOI: 10.1038/s41598-020-76234-8
|View full text |Cite
|
Sign up to set email alerts
|

RNA seq analyses of chicken reveals biological pathways involved in acclimation into different geographical locations

Abstract: Transcriptome expression reflects genetic response in diverse conditions. In this study, RNA sequencing was utilized to profile multiple tissues such as liver, breast, caecum, and gizzard of Korean commercial chicken raised in Korea and Kyrgyzstan. We analyzed ten samples per tissue from each location to identify candidate genes which are involved in the adaptation of Korean commercial chicken to Kyrgyzstan. At false discovery rate (FDR) < 0.05 and fold change (FC) > 2, we found 315, 196, 167 and 198 gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…Indeed, many pathways and metabolites had been found to be activated in order to maintain homeostasis and react to issues caused by oxidative stress. In more detail, glycogenolysis and gluconeogenesis (as also shown by Kumar et al [ 148 ]) as well as fat deposition, glycosylation, and glutathione production were increased. Finally, the transcriptome data have shown a trend to slow down the cell cycle in order to allow time for repairing DNA damage caused by HS [ 147 ] (Jastrebski et al, 2017).…”
Section: A Step Over Hspssupporting
confidence: 62%
“…Indeed, many pathways and metabolites had been found to be activated in order to maintain homeostasis and react to issues caused by oxidative stress. In more detail, glycogenolysis and gluconeogenesis (as also shown by Kumar et al [ 148 ]) as well as fat deposition, glycosylation, and glutathione production were increased. Finally, the transcriptome data have shown a trend to slow down the cell cycle in order to allow time for repairing DNA damage caused by HS [ 147 ] (Jastrebski et al, 2017).…”
Section: A Step Over Hspssupporting
confidence: 62%
“…RNA-Seq can help us to understand this question [ 15 ]. The study of different breeds of poultry from different geographical locations has been reported [ 16 ]. In this study, we implemented an RNA-Seq approach to compare transcriptome profiling of two chicken breeds.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, studies of differentially expressed genes as a transcriptional response of the genome to various environmental stimuli or physiological/pathological conditions have been one of the most modern approaches (Gmoshinsky et al, 2018). The transcriptome of birds has previously been studied in connection with immunity (Wahl, et al, 2004), adaptive potential (Kumar et al, 2020) and meat productivity (Zhang, et al, 2021). However, experiments to study the effect of glyphosate on the transcriptome of living organisms have not been conducted before.…”
Section: Introductionmentioning
confidence: 99%